Prognostic impact of preoperative platelets to lymphocytes ratio (PLR) on survival for oesophageal and junctional carcinoma treated with neoadjuvant chemotherapy: A retrospective monocentric study on 153 patients. Issue 10 (October 2015) - Messager, M.; Neofytou, K.; Chaudry, M.A.; Allum, W.H.
Abstract This study was designed to investigate the prognostic impact of elevated platelet to lymphocyte ratio (PLR) on survival for oesophageal and junctional adenocarcinoma (OJA) treated with neoadjuvant chemotherapy in a curative intent. From 2004 to 2014, 153 consecutive patients with OJA were included. PLR was measured at first diagnosis. Receiver Operating Characteristic curve analysis was performed to determinate PLR threshold. Cox multivariate model was used to assess correlation between PLR and survival. Cut-off value for PLR was 192, which identified 2 groups of patients: low (n = 122) and high PLR value (n = 31). Both groups were comparable by patient (age, sex, ASA score) and tumour characteristics (differentiation, TNM stage, location). Five year overall survival (OS) was 65%. OS and DFS were reduced in the high PLR group: p = 0.019 and p = 0.016, respectively. PLR was associated with increased recurrence (54.8% vs. 35.2%, p = 0.046) and cancer-related death (41.9% vs. 23.8%, p = 0.043) rates. On multivariate analysis, elevated PLR was associated with decreased DFS (HR = 2.85, 95%CI = 1.54–5.26, p = 0.001) and OS (HR = 2.47, 95%CI = 1.21–5.01, p = 0.012). This study demonstrates that elevated PLR is associated with poor OS and DFS for OJA treated with a curative intent and has the potential to be a useful prognostic biomarker for treatment planning.